A Review on Synthesis of Plant-Mediated Metal Nanoparticles for Fabric Coating - Wan Norfazilah, Wan Ismail; Hartina, Mohd Yusop (Institut Kimia Malaysia, 2021)
Biosynthesis, or also known as green synthesis method, has received an enormous attention from the scientific community over the physical and chemical synthesis methods for the production of metal or metal oxide nanoparticles (NPs). Physical and chemical syntheses are typically expensive and generate a large number of hazardous by-products which can cause toxicity to either humans or the environment. Thus, biosynthesis is an alternative for production of NPs. Biosynthesis involves the use of plant extracts and natural bio-resources such as microorganisms and enzymes. It has been demonstrated that the biosynthesis method is suitable for large-scale production since it is simple, cheap, easy, fast, non-toxic, and environmentally friendly. This review mainly focuses on the synthesis of plant-mediated metal NPs for fabric coating. Importantly, the characteristics of the NPs and their applications after fabrication onto the fabrics are also highlighted. The morphology and size of the NPs are influenced by the concentration of plant extracts, control of metal salt concentration, temperature, and pH. This review also summarizes the advantages, limitations, and future challenges of biosynthesis towards the production of fabric coatings. There are several advantages in utilizing green substances, including moderate operation conditions with a minimal use of toxic chemicals and low energy consumption.